A infância no Pampa: Contos gauchescos e Lendas do Sul - Marangoni, Marli Cristina Tasca (My University, 2014)
This dissertation investigates the construction of regional identities from the infancy representations verified in Contos gauchescos and Lendas do Sul, by João Simões Lopes Neto. For that, there have been discussions about the relations between adult and infantile universes, the roles of child character, the ways to refer and characterize the child, as well as the expected and possible trajectories in the narrative. In this manner, this study demonstrates the predominant constitution of the infantile individual as an heir of a socio-cultural tradition, knowing that such identifying reference inhibits the renewal of the social conception of infancy in the shown society. Therefore, an approach to the literary text is shaped supported by History and Anthropology, contributing to an interdisciplinary perspective on regionality matters, within the ambit of cultural studies.
Esta Dissertação investiga a construção de identidades infantis regionais, a partir de representações da infância verificadas em Contos gauchescos e Lendas do Sul, de João Simões Lopes Neto. Para tanto, são discutidas as relações entre os universos adulto e infantil, os papéis destinados à personagem mirim, os modos de referir e caracterizar a criança, bem como suas trajetórias esperadas e possíveis no mundo narrado. Desse modo, o presente estudo demonstra a predominante constituição do sujeito infantil como herdeiro de uma tradição sócio-cultural, entendendo-se que tal referência identitária inibe a renovação da concepção social de infância, na sociedade representada. Configura-se, assim, uma abordagem ao texto literário subsidiada por aportes da História e da Antropologia, contribuindo para uma perspectiva interdisciplinar sobre a problemática da regionalidade, no âmbito dos estudos culturais.
Keywords: Ciências humanas; Infância; Cultura; Região; Identidade; Representação; Infancy; Culture; Region; Identity; Representation; Relações familiares; Cultura regional; Contos gauchescos